EVOLVING LANDSCAPE EDUCATION: REFORM MEASURES FOR MIXED TEACHING IN ECOLOGICAL LANDSCAPE DESIGN - Rossi , Lucia; Mateo , Gonzalez (Top Educational Review Journal (TERJ), 2024)
Landscape ecological design stands as a pivotal component of environmental design and landscape architecture curricula. Its purpose is to equip students with the adept utilization of diverse ecological design patterns and methodologies, rooted in the study of landscape design theories and practical techniques. This educational emphasis fosters students’ comprehensive design prowess, providing them with a robust foundation to undertake real-world project planning. With the nation’s active promotion of urban and rural development coupled with the ongoing advancement of ecological civilization, the landscape industry is poised for a broader future. Consequently, higher education institutions must prepare a cadre of highly skilled, multidisciplinary professionals to meet the demands of this burgeoning field. In this context, the integration of mixed teaching methods has emerged as the current educational trend and the trajectory of design education’s evolution. As a result, the efficient and strategic use of information resources to facilitate the seamless implementation of mixed teaching in ecological landscape design has become a pressing concern within landscape professional education.